2007
DOI: 10.1007/s00705-007-1006-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue tropism of salmonid alphaviruses (subtypes SAV1 and SAV3) in experimentally challenged Atlantic salmon (Salmo salar L.)

Abstract: Diagnosis of SAV infections has traditionally been based upon clinical observations together with a set of histopathological findings in exocrine pancreas, heart and skeletal muscle, but recently, real-time RT-PCR assays have been developed as a supplement for the detection of SAV. The aim of this study was to determine tissue tropism of SAV1 and SAV3 in Atlantic salmon Salmo salar L. in order to identify the most suitable tissues for real-time RT-PCR diagnostic assays. The results indicated that the pseudobra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 29 publications
9
65
0
Order By: Relevance
“…Several studies have shown heart tissue to be one of the most appropriate tissues for detecting SAV during all stages of infection (also persistent infections) (Graham et al 2006, Christie et al 2007, Andersen et al 2007; for this reason, only heart tissue was processed for molecular testing. Approximately 5 mg of homogenised tissue was used for ex traction of total RNA (MagAttract M48 RNA Tissue Kit, Qiagen) using the M48 BioRobot (Qiagen).…”
Section: Sav Rt-qpcr and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown heart tissue to be one of the most appropriate tissues for detecting SAV during all stages of infection (also persistent infections) (Graham et al 2006, Christie et al 2007, Andersen et al 2007; for this reason, only heart tissue was processed for molecular testing. Approximately 5 mg of homogenised tissue was used for ex traction of total RNA (MagAttract M48 RNA Tissue Kit, Qiagen) using the M48 BioRobot (Qiagen).…”
Section: Sav Rt-qpcr and Sequencingmentioning
confidence: 99%
“…Through experimental studies, SAV has been shown to survive for 5.7 d at 10°C in sterile saltwater with organic loading ). Moreover, viral RNA has been shown to persist in tissues for extended periods (Andersen et al 2007, Christie et al 2007, Graham et al 2010, Jansen et al 2010), potentially posing an infection risk to healthy fish.…”
Section: Introductionmentioning
confidence: 99%
“…The highest viral load is found in the heart and pancreas (Andersen et al, 2007;Xu et al, 2012). To compare viral infection levels and corresponding pathological changes, 50 Atlantic salmon parr were infected by intramuscular injection with 10 5.17 TCID 50 of H10 P3 and in a parallel tank a similar infection was performed using H10 P14 at the same infection dose.…”
Section: P11mentioning
confidence: 99%
“…Tissue lesions include degeneration and necrosis of cardiomyocytes, pancreatic acinar cell loss and subsequent skeletal muscle degeneration (McLoughlin et al, 2006;Mcvicar, 1987). Virus has been detected in a wide range of tissues (Andersen et al, 2007), and it has been suggested that pancreas, heart, kidney and spleen are infected at about the same time (Xu et al, 2012). However, the virus replicates with highest viral load in the pancreas and heart (Andersen et al, 2007;Xu et al, 2012), and the pancreas is suggested as the preferred site of replication (McLoughlin & Graham, 2007;McLoughlin et al, 1996;Xu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation